2011
DOI: 10.4258/hir.2011.17.3.172
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Electronic Medical Records and Decision Support Systems in Korea

Abstract: ObjectivesTo examine the current status of hospital information systems (HIS), analyze the effects of Electronic Medical Records (EMR) and Clinical Decision Support Systems (CDSS) have upon hospital performance, and examine how management issues change over time according to various growth stages.MethodsData taken from the 2010 survey on the HIS status and management issues for 44 tertiary hospitals and 2009 survey on hospital performance appraisal were used. A chi-square test was used to analyze the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 11 publications
0
38
2
Order By: Relevance
“…Although a survey study that only included tertiary hospitals in Korea found just 27.3% of hospitals with clinical information systems also had CDS systems,16 we found that all of our responding hospitals had CDS.…”
Section: Methodscontrasting
confidence: 67%
“…Although a survey study that only included tertiary hospitals in Korea found just 27.3% of hospitals with clinical information systems also had CDS systems,16 we found that all of our responding hospitals had CDS.…”
Section: Methodscontrasting
confidence: 67%
“…People who live in urban areas adopt EMR system more than people who live in rural areas (Kazley & Ozcan, 2007). Chae, Yoo, Kim, & Chae, 2011;Cotea, 2010;Ford, 2009Ford, , 2012aFord, , 2012bJha et al, 2009;Kazley & Ozcan, 2007;Li & West-Strum, 2010;Menachemi et al, 2007Menachemi et al, , 2012Rao et al, 2011;Teufel, Kazley, Andrews, Ebeling, & Basco, 2013 Resource dependence theory 8 4 Reputation of practice "As a current nonadopter hospital scans its environment and seeks to establish legitimacy by emulating prestigious role models, we expect that EMR adoption by celebrity hospitals will exert a relatively more potent social influence. ", "Within the population of adopters, the infectiousness of celebrity adopter hospitals is stronger than the infectiousness of noncelebrity adopter hospitals" (Angst et al, 2010(Angst et al, , p. 1226 Social proximity to prior adopted hospital (membership to social network) "Social proximity or membership in a social group is also important for contagious influence."…”
Section: Kazley and Ozcan 2007mentioning
confidence: 99%
“…1 Surveys on EMR adoption rate in tertiary hospitals in South Korea reported 50% to 77% in 2009 and 2010. 24,25 Nursing students of South Korea, however, use EMRs mostly to retrieve patient information, and much less for electronic documentation in the clinical practicum. As no study has reported on the use of AEMRs for clinical practicum in South Korea to date, the purpose of this study was to explore how students, new nurses, clinical instructors, and faculty perceive the integration of AEMRs into the undergraduate clinical practicum.…”
mentioning
confidence: 99%